The Efficacy of Spell Check Packages Specifically Designed for Second Language Learners of Spanish. - BIazquez, Migucl; Fan, Catherine (Pertanika Journal of Social Sciences & Humanities, 2019)
Generic spelling checkers (GSCs), such as the one included in Microsoft Word, might seem appropriate for second language (L2) learners of Spanish to correct their writing. However, previous applied linguistics researchers point out that these proof-readers are designed primarily for native writers; they automatically correct some mistakes or provide alternatives, while sometimes failing to detect L2 learners' errors. This study evaluates the efficacy of spell-check packages developed for L2 learners to overcome these limitations. Thirty compositions written by learners of Spanish as a Foreign Language (SFL) were randomly chosen from a corpus. Spelling mistakes in the compositions were analysed, categorised and inputted into three specially designed spell checkers. Their efficacy in detecting and providing appropriate feedback was compared with a GSC. The results suggest that, despite detecting more than 85% of the errors, all the platforms fail to give the appropriate alternative for one third of the spelling errors. Surprisingly, the GSC provided the right alternative more frequently (67%). Additionally, the feedback provided by the specialised spell checkers is limited to a list of potential alternatives. Future iterations of spell checkers should include an expanded database of frequent L2 spelling errors for comparison and feedback that is tailored to L2 learners of Spanish and teaches them how to avoid future mistakes.